Natural convection of a nanofluid between two eccentric cylinders saturated by porous material: Buongiorno's two phase model. (December 2018) - Izadi, Mohsen; Sinaei, Sara; Mehryan, S.A.M.; Oztop, Hakan F.; Abu-Hamdeh, Nidal
Highlights: The study concerns with a numerical study on natural convection of different nanofluids in a porous medium. The Buongiorno's model was utilized to track the nanoparticles concentration. Thermophoresis and Brownian parameter have no significant effect on isothermal lines and the streamlines. Abstract: This paper concerns with a numerical study on heat transfer by natural convection of different nanofluids inside a porous medium between two horizontal eccentric cylinders. The Buongiorno's model was utilized to track the nanoparticles concentration. Heat transfer by natural convection of water-copper, water-diamond and water–silicon dioxide nanofluids inside a porous medium between two cylinders was studied. A set of characteristic equations were solved using finite element method. Range of parameters which are studied are Ra = 10 3 -10 6, Da = 10 −6 -10 −3, ε = 0.1–0.9 and volume fractions of 0.0–0.1, Nr = Nt = Nb = 0.1–0.5, and Le  = 1–10. The porous medium was analyzed by Darcy-Brinkman model. The results showed that thermophoresis parameter and Brownian parameter have no significant effect on isothermal lines and the streamlines. The probability of collision of nanoparticles decreases with increasing the Lewis number, which consequently decreases the average Nusselt number. The maximum and minimum enhancement in natural convection was detected in water-diamond and water–silicon dioxide respectively.